Primitive neuroectodermal tumor (neuroblastoma) arising in sciatic nerve of a child - Nesbitt, Kenneth A.; Vidone, Romeo A. (Cancer, 1976)
A well‐documented case of a primitive neuroectodermal tumor (neuroblastoma) arising in the sciatic nerve of a 6‐year old boy is presented. After radical surgical excision of the tumor, followed by chemotherapy, the child remained clinically free of disease for 20 months. Tumor then recurred locally followed by widespread dissemination. He expired 2 years postoperatively. The literature on this type of rare and controversial tumor of peripheral nerves is reviewed. Only a very few reported cases are considered fully acceptable. Interest in this subject, and adequate documentation of future reported cases may lead to a better understanding of this class of malignant tumors.